2021
DOI: 10.3389/fnhum.2021.651168
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Burst-Cycling Deep Brain Stimulation for Freezing of Gait in Parkinson’s Disease

Abstract: Background: Freezing of gait (FOG) is a common symptom in Parkinson’s disease (PD) and can be difficult to treat with dopaminergic medications or with deep brain stimulation (DBS). Novel stimulation paradigms have been proposed to address suboptimal responses to conventional DBS programming methods. Burst-cycling deep brain stimulation (BCDBS) delivers current in various frequencies of bursts (e.g., 4, 10, or 15 Hz), while maintaining an intra-burst frequency identical to conventional DBS.Objective: To evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…A later study found that the implementation of a cycling stimulation pattern improved FOG in one PD patient who had developed tolerance to DBS ( Dayal et al, 2021 ). On the other hand, Wong et al (2021) did not find significant differences between cycling and conventional HFS in the treatment of FOG in patients with PD. Montgomery et al found that continuous HFS of the STN provided greater symptom relief than burst cycling, showing a linear relationship between cycling interval and motor performance, with increasing efficacy of cycling from 0.1 to 0.5 s, both of which were inferior to continuous HFS.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…A later study found that the implementation of a cycling stimulation pattern improved FOG in one PD patient who had developed tolerance to DBS ( Dayal et al, 2021 ). On the other hand, Wong et al (2021) did not find significant differences between cycling and conventional HFS in the treatment of FOG in patients with PD. Montgomery et al found that continuous HFS of the STN provided greater symptom relief than burst cycling, showing a linear relationship between cycling interval and motor performance, with increasing efficacy of cycling from 0.1 to 0.5 s, both of which were inferior to continuous HFS.…”
Section: Resultscontrasting
confidence: 60%
“…Of the excluded studies, five were reviews, three did not use ILS, one was in silico (i.e., no human subjects), one was a video, and one was not in English. For burst cycling, the search found 32 studies, of which 14 were included ( Montgomery, 2005 ; Velasco et al, 2007 ; Tai et al, 2011 ; Kuncel et al, 2012 ; Min et al, 2013 ; Boongird et al, 2016 ; Huang et al, 2019 ; Enatsu et al, 2020 ; Kaufmann et al, 2020 ; Dayal et al, 2021 ; Vázquez-Barrón et al, 2021 ; Wong et al, 2021 ; Dalic et al, 2022 ; Loeffler et al, 2022 ). Of the excluded studies, five did not report clinical outcomes (e.g., imaging study with fMRI), four did not use burst cycling, four did not use DBS, three were reviews, one was a conceptual study with no human subjects, and one combined VNS and DBS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have been made to bring such therapeutic paradigms to DBS programming ( 163 ), but current evidence is preliminary and based on in-clinic observations and may require further testing to address the neuroplasticity effects and long-term observations during chronic stimulation. Additional studies in this area also seek to investigate different burst frequencies for axial symptoms with significantly less battery consumption and fewer side effects ( 164 ). However, it is also important to note that not all brain targets benefit from cycling.…”
Section: Conventional Stimulation Parametersmentioning
confidence: 99%
“…An alternative theory is that DBS entrains neural activity 8 , which interferes with individual neuronsʼ ability to respond to synaptic inputs and thereby creates an informational lesion 19 that disrupts pathological network patterns. The effects of DBS on network dynamics have inspired the exploration of stimulation pulse patterns that may better engage plasticity mechanisms 20 , 21 , and the development of closed-loop DBS systems that target network-level pathological electrical field features in epilepsy 2 , 21 and Parkinson’s disease 5 , 6 , 22 , 23 . Recent long-term clinical studies reported an impressive reduction of seizure frequency by closed-loop responsive neurostimulation that targeted subject-specific abnormal intracranial electroencephalogram patterns in epilepsy patients 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%